In-Silico Cloning and Analysis of Divalent Subunit OMP31-SODc Proteins As A Prophylaxis Vaccine Against Brucella melitensis Infection - Wijaya, Sri Kartika; Kusumawati, Arizah; Wardiana, Andri; Rubiana, Yana; Husnaa, Ulfatul; Santoso, Adi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
The urgency to develop a new protein based subunit vaccine candidate against Brucella was provoked by its frequent infection to human and lives stock. Since Brucella melitensis is found as the most species isolated from human, thus the outer membrane of the Brucella melitensis become prominent subcellular location for searching promising antigen to be developed as vaccine target due to its interaction with cell host. Among other proteins suggested by Vaxign program, the OMP31 is found as a promising candidate. Moreover, analysis on other subcellular location leads our interest to SODc protein, which is expected to support the OMP31 in triggering immune response. The OMP31-SODc divalent vaccine candidate was analysed in-silico to predict its stable three-dimensional structure, cloning process and expectation on the ease during expression, purification and the protein vaccine delivery to develop expected immune response.